Validation of a targeted next-generation sequencing panel for tumor mutation burden analysis: results from the Onconetwork Immuno-Oncology Consortium - Fenizia, Francesca; Alborelli, Ilaria; Costa, Jose Luis; Vollbrecht, Claudia; Bellosillo, Beatriz; Dinjens, Winand; Endris, Volker; Heydt, Carina; Leonards, Katharina; Merkelback-Bruse, Sabine; Pfarr, Nicole; van Marion, Ronald; et al. (The journal of molecular diagnostics, 2021)
Tumor mutation burden (TMB) is evaluated as a biomarker of response to immunotherapy. We present the efforts of the Onconetwork Immuno-Oncology Consortium to validate a commercial targeted sequencing test for TMB calculation. A three-phase study was designed to validate the Oncomine Tumor Mutational Load (OTML) assay at nine European laboratories. Phase 1 evaluated reproducibility and accuracy on seven control samples. In phase 2, six formalin-fixed, paraffin-embedded samples tested with FoundationOne were reanalyzed with the OTML panel to evaluate concordance and reproducibility. Phase 3 involved analysis of 90 colorectal cancer samples with known microsatellite instability (MSI) status to evaluate TMB and MSI association. High reproducibility of TMB was demonstrated among the sites in the first and second phases. Strong correlation was also detected between mean and expected TMB in phase 1 (r2 = 0.998) and phase 2 (r2 = 0.96). Detection of actionable mutations was also confirmed. In colorectal cancer samples, the expected pattern of MSI-high/high-TMB and microsatellite stability/low-TMB was present, and gene signatures produced by the panel suggested the presence of a POLE mutation in two samples. The OTML panel demonstrated robustness and reproducibility for TMB evaluation. Results also suggest the possibility of using the panel for mutational signatures and variant detection. Collaborative efforts between academia and companies are crucial to accelerate the translation of new biomarkers into clinical research.